MODULATORY EFFECT OF FENUGREEK (TRIGONELLA FOENUM GRAECUM) SEED EXTRACT ON SALIVARY GLANDS LIPOFUSCHINOGENESIS IN AGINGACCELERATED MALE MICE. - V. M. DESHMUKH; M. V. WALVEKAR; S.R. DESAI (International Journal of Pharma and Bio Sciences, 2014)
The present investigation was undertaken to evaluate antioxidative property of fenugreek seed extract (FSE) on lipid peroxidation and fluorescence product in salivary glands of mice. The aging was induced by D-galactose (Dg). Adult albino male mice (Mus musculus L) were divided into four groups viz. 1)Control group received subcutaneous injection of 0.5 ml sterile water/day for 20 days 2) Dg- treated group received subcutaneous injection of 0.5 ml of 5% Dg/ day for 20 days 3)Protective group received Dg+ FSE (50mg/kg BW) by subcutaneous injection for 20 days 4)Curative group received Dg then after FSE (50mg/kg BW) subcutaneously for next 20days.After the completion of treatment submandibular and sublingual glands were removed and used for the estimations of lipid peroxidation in the form of malondialdehyde (MDA) and fluorescence product. The MDA level and fluorescence product in both glands were significantly raised in Dg treated group as compared to control group but after the treatment of FSE significant decrease in both parameters in protective and curative group was observed. The results of curative group were more satisfactory as compared to the protective group indicating that FSE give protection against the aging.